2008
DOI: 10.1074/jbc.m801480200
|View full text |Cite
|
Sign up to set email alerts
|

A Consensus Sequence for Binding of SmcR, a Vibrio vulnificus LuxR Homologue, and Genome-wide Identification of the SmcR Regulon

Abstract: Quorum sensing has been implicated as an important global regulatory system controlling the expression of numerous virulence factors in bacterial pathogens. In the present study, DNA targets of SmcR, a Vibrio vulnificus LuxR homologue, were selected from a random pool of DNA fragments by using a cycle selection procedure consisting of in vitro DNA-SmcR interaction, purification of SmcR-DNA complexes, and PCR amplification of SmcR-bound DNA. The amplified DNA fragments were cloned and analyzed separately by ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 32 publications
3
79
0
Order By: Relevance
“…In this study, we showed that SmcR represses the transcription of the vvs genes by directly binding to the promoter region. The SmcR binding site (5Ј-AATGAT-GTTAATGATAATTATT-3Ј) in the vvsA promoter is a mirror image of the known SmcR binding consensus sequence (5Ј-TTATTGATWWRWTWNTNAATAA-3Ј) (18). The vvsA site has a 22-bp inverted repeated sequence just like the consensus sequence, suggesting that the size and the inverted repeat feature may be more important for SmcR binding than the base pairs per se.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we showed that SmcR represses the transcription of the vvs genes by directly binding to the promoter region. The SmcR binding site (5Ј-AATGAT-GTTAATGATAATTATT-3Ј) in the vvsA promoter is a mirror image of the known SmcR binding consensus sequence (5Ј-TTATTGATWWRWTWNTNAATAA-3Ј) (18). The vvsA site has a 22-bp inverted repeated sequence just like the consensus sequence, suggesting that the size and the inverted repeat feature may be more important for SmcR binding than the base pairs per se.…”
Section: Discussionmentioning
confidence: 99%
“…5B), indicating that binding of SmcR to the vvsA promoter is specific. A 22-bp consensus sequence for SmcR binding has been proposed based on examination of promoter regions of V. vulnificus genes directly regulated by SmcR (5Ј-TTATTGATWWR-WTWNTNAATAA-3Ј; W represents A or T, R represents G or A, N represents any nucleotide) (18). However, a similar sequence is not apparent in the vvsA promoter region.…”
Section: Iron Represses Vvsa Transcription In the Presence Of Fur-itmentioning
confidence: 99%
See 1 more Smart Citation
“…HapR regulates approximately 4.1% of the V. cholerae El Tor genome (73). For V. vulnificus, a 121-gene SmcR regulon has been predicted by using a consensus binding sequence that was generated by DNA footprinting assays (35). A screen of random genomic V. harveyi DNA fused to promoterless green fluorescent protein (GFP) identified 71 autoinducer-regulated genes, all of which were LuxR dependent (64).…”
Section: Discussionmentioning
confidence: 99%
“…We made progress in determining how V. harveyi LuxR controls gene expression by defining its DNA-binding site and decoding its regulon (Waters and Bassler 2006;Lee et al 2008;Pompeani et al 2008), but we understand comparatively little about AphA in V. harveyi. However, the mechanisms of AphA repression and activation have received attention in V. cholerae, which should guide our continued analyses (Kovacikova and Skorupski 2001;Kovacikova et al 2003Kovacikova et al , 2004Kovacikova et al , 2005Kovacikova et al , 2010De Silva et al 2005;Yang et al 2009).…”
Section: Discussionmentioning
confidence: 99%